Role of race in kidney transplant outcomes in children with focal segmental glomerulosclerosis. (27th July 2016) - Guan, Ivan; Singer, Pamela; Frank, Rachel; Chorny, Nataliya; Infante, Lulette; Sethna, Christine B.
Abstract: It is well established that racial differences exist in kidney transplant outcomes; however, there are no studies which focus on the role of race in transplant outcomes specifically in children diagnosed with FSGS. Associations between race and transplant outcomes in FSGS children were evaluated using the Organ Procurement and Transplantation Network database from 2000 to 2012. Recipients aged 2–21 years who received a kidney‐only transplant were included. Multivariate regression models were used to evaluate transplant outcomes by race. Five hundred and thirty‐six recipients (59.7% male, 15.6±3.9 years) were black and 1134 (55.7% male, 14.3±5.0 years) were non‐black. Graft survival was significantly shorter in the black group (4.2±3.1 vs 4.6±3.3 years, P =.005). Black race was associated with significantly higher risk of graft failure (HR 1.34, 95% CI=1.21–1.49, P <.0001), acute rejection (OR 1.66 95% CI=1.39–1.97, P <.0001), and delayed graft function (OR 1.51, 95% CI=1.33–1.72, P <.001) compared to non‐black race. There were no significant differences in mortality, prolonged hospitalization, or FSGS recurrence between groups. Race is a significant predictor for worse transplant outcomes in children with FSGS.